GUIDELINES AND BEST PRACTICE RECOMMENDATIONS ON CONTRACEPTION AND SAFE ABORTION CARE SERVICE PROVISION AMID COVID-19 PANDEMIC: SCOPING REVIEW - Asfaw, Mariamawit; Tolu, Lemi Belay; Urgie, Tadesse; Nigatu, Balkachew; Bekele, Delayehu; Asrat Shiferaw, Matiyas (Ethiopian Journal of Reproductive Health, 2021)
Abstract Introduction: Policy makers and health professionals prefer to use summarized evidence of practice recommendations. The aim of this scoping review is therefore to identify available practice recommendations on contraception and safe abortion care service provision during the COVID-19 pandemics. Methods: We searched guideline databases and websites of professional associations and international organizations working on sexual and reproductive health. Additionally, we searched: PubMed, EMBASE Google Scholar MedRxiv and Research Square. We included English records labelled guideline, or recommendation, or consensus, or practice parameter, or position papers on contraception and safe abortion care service practice during the COVID-19 pandemics. Data extraction was done by two independent reviewers using a customized tool that was developed to record the key information of the source that is relevant to the review question. The difference between the two authors on data extraction was resolved by discussion. Results: Fourteen records on safe abortion care and thirteen records on contraception service were identified. Identified recommendations were categorized into thematic areas. The records addressed approaches to the safe medication and surgical abortion, self-serving family planning and long term and reversible contraception. Conclusions: Consensus statements and recommendations consistently stated that there should be access to contraception service and safe abortion care during the COVID-19 pandemics. The practice recommendations focus on innovative ways of service provision to minimize patient and staff exposure to COVID-19 as well as alleviate the burden on the health care system. These include utilizing telemedicine or digital health and community/home-based care or self-care Keywords: COVID-19, Pandemic, Reproductive health, Abortion, Contraception.